Comparação da força de preensão palmar e composição corporal entre mulheres mastectomizadas ou não - Manduca, Mariana dos Santos Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Introduction: Loss of muscle strength may represent a burden on everyday tasks significantly compromising the quality of life for mastectomy patients. In addition to the reduced strength of the upper limb, has been shown in mastectomy patients and difficulties in reducing grip. Objectives: To analyze the possible differences in grip strength among women undergoing breast cancer surgery and to compare the body composition. Methods: In the control group (CG n = 46) women participated in the community of FCT / UNESP aged 35 to 70 years without acute orthopedic pathologies. In the experimental group (EG n = 49) participated in women undergoing surgery for breast cancer, without bilateral lymphedema and independent of time and type of surgery. Were evaluated by dynamometer, by Dual Energy X-ray absorptiometry (DEXA) and physical assessment. Results: We observed significant differences in grip strength (p = 0.000), when the group after mastectomy compared with the control group and the radical mastectomy surgery left and quandrandectomia left (p = 0.004). Regarding the presence of lymphedema, statistical difference was observed in the composition of lean mass and trunk fat (p = 0.05). Conclusion: The results of this study suggest that the experimental group are lower grip strength and trunk lean body mass when compared with the control group. The experimental group showed higher values of fat mass when there was presence of lymphedema
Keywords: Fisioterapia; Mastectomia; Palpação; Corpo - Composição